Sound absorption of microperforated panel made from coconut fiber and polylactic acid composite - Chin Vui Sheng, Desmond Daniel; Yahya, Musli Nizam; Che Din, Nazli (Taylor and Francis Ltd., 2022)
This paper highlights the sound absorption performance of microperforated panel (MPP) made from coconut fiber and polylactic acid (PLA) composite named as biocomposite microperforated panel (BMPP). Coconut fiber was used to produce BMPP specimen and PLA was used as matrix. Impedance tube method was employed to identify the sound absorption performance of BMPP specimen while a porosity tester was used to determine the porosity of BMPP specimen. Comparison on the sound absorption performance between BMPP and steel MPP will be discussed in this paper. It has been found that BMPP with different composition percentage of coconut fiber and PLA possessed different sound absorption performance mainly due to the existence of pores and tortuous structure within the specimen itself. Scanning electron microscope (SEM) scan was performed to further analyze the structure of BMPP specimen.